Mechanism of the Direct Reduction of Chromite Process as a Clean Ferrochrome Technology - Paktunc, Dogan; Coumans, Jason P.; Carter, David; Zagrtdenov, Nail; Duguay, Dominique (ACS Engineering Au, 2024)
Direct reduction of chromite (DRC) is a promising alternative process for ferrochrome production with the potential to significantly reduce energy consumption and greenhouse gas emissions compared to conventional smelting. In DRC, chromium (Cr) and iron (Fe) from chromite ore incongruently dissolve into a molten salt, which facilitates mass transfer to a carbon (C) reductant where in situ metallization occurs. Consequently, ferrochrome is produced below the slag melting temperatures, achieving substantial energy savings relative to smelting. However, there are significant knowledge gaps in the kinetics, Cr solubility, speciation, and coordination environment which are critical to understanding the fundamental mechanisms of molten salt-assisted carbothermic reactions. To address these knowledge gaps, we performed pyrometallurgical experiments with variable temperature and residence times and analyzed the composition of chromite, ferrochrome, and slag products along with determining the speciation of Cr. Our results indicate that the DRC mechanism can be explained by the following sequential steps: (1) incongruent dissolution of chromite, (2) reduction of dissolved Cr in molten salt/slag, (3) transport of Cr and Fe species in molten media, and (4) reduction on C particles and metallization as Cr–Fe alloys. The discovery of four types of reduced Cr species in the slag indicates that the reduction of Cr3+ to Cr2+ and Cr0 occurred in the molten phase before metallization on solid carbon particles. Thermodynamically, the reduction of CrO(l) to Cr metal is more feasible at a lower temperature than it is for Cr2O3(l) corroborating the accelerated reduction efficiency of the DRC process.